INTERNATIONAL REGIMES AND TRANSPORTATIONS; TIR REGIME AND ITS MAIN TRAITS - Ciprian Beniamin BENEA; Adrian NEGREA (Oradea Journal of Business and Economics)
The paper aims to indicate that the processes of regionalization and globalization were in a great manner determined and influenced by collaboration and coordination among states. But collaboration and cooperation couldn’t have been promoted in a sustainable manner in the absence of international regimes; their creation is indispensable and it is responsible for the world we know it. Collaboration in order to attain common interests has been facilitated by international regimes’ creation and international organization, as framework for multilateral negotiations. Transport area is an area where states’ interests related to security and welfare overlap; collaboration for infrastructure construction has a very technical character, but it is covered by a legal structure which provide common principles, norms, rules, and procedures applicable in a specific transport area. This is in fact exactly the international regime, which facilitates common interests’ promotion through a steady horizontal, vertical and oblique negotiation process. It brings together international regimes, international organizations, and multilateral negotiations. One of the most successful multilateral negotiations is related to road transport: it is TIR Regime and Convention, which have promoted public and private interests with a great success. Since its creation in 1959, its principles and norms were expanded geographically and technically, including today the container transport which has global coverage. The paper carries reader through what international regime is, how it works through multilateral negotiations carried under the aegis of permanent international institutions, the main traits of regimes in transportation, following with a more detailed presentation of principles and norms specific to TIR regime.